42y=66

Simple and best practice solution for 42y=66 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 42y=66 equation:


Simplifying
42y = 66

Solving
42y = 66

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Divide each side by '42'.
y = 1.571428571

Simplifying
y = 1.571428571

See similar equations:

| -8x-5y=-11 | | 81-x=27 | | 9a=a+60 | | 2b-b^2-15=0 | | 2(2x-8)-5=2(x-3)-1 | | 78507+11.25x=20885+23x | | 6N+6J=N | | 2a-11=3(a+1)+16a+5 | | 3x^2-13w-6w^2=0 | | v=2v-73 | | 7n+6=13+7n | | 16=-2(x+4) | | 5-13w-6w^2=0 | | 4u+18=2u+66 | | 0.20=ln(y) | | .25(x+4)=32 | | 9x^2-36=y | | 8u^2+1u-9=0 | | 28-8k=4(-1-k) | | 6x+-9=2x+7 | | 17x-7=13x+1 | | 6x+-9=2x+-7 | | 3.2=y+5.4 | | 9x-(6x+9)=7x-29 | | 5m-4=3(m+6) | | 4a-7=7(a+1)+14a+6 | | t+30=1 | | 5-2(2m+3)=15 | | 2(10x+3)=5(4x-7) | | -23=5k+7k | | 0.6x=0.4x+50 | | 2(5-3x)=9-6x |

Equations solver categories